PENINGKATAN KEMAMPUAN MENENTUKAN ALUR, PENOKOHAN DAN LATAR DALAM CERPEN â€œROBOHNYA SURAU KAMIâ€ KARYA ALI AKBAR NAVIS MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS XI 1 SMKN AMPIBABO - Ambar, Ambar (BAHASANTODEA, 2017)
The problem in this research is "how is the implementation of STAD cooperative learning to improve the ability of class XI student of SMK 1 Ampibabo Define plot, characterization and background in the short story "Robohnya Surau Kami" by Ali Akbar Navis? How peningtkatan ability of class XI student of SMK 1 Ampibabo in Define groove, characterization and background in the short story "Robohnya Surau Kami" by Ali Akbar Navis with the implementation of cooperative learning STAD ?. This research is a classroom action research subject class XI student of SMKN 1 Ampibabo. This research was conducted in two cycles, with the results of research on teacher observation results of the first cycle 68%, while 16.6% student activity observation with the results of the evaluation of learning outcomes students' average score of 6.6, with a 38% percentage of completeness. Referring to KKM applicable in SMK 1 Ampibabo average value of 70 with classical completeness 80%, the result of cycle I have not reached the standard of completeness. Implementation of the second cycle showed significant improvements. The results of observations of teachers increased to 100%, observation of student activity 66.7% 33.3% good and excellent categorized with the evaluation results determine the student's ability plot, characterization and background stories that the average value obtained by the students of 7.9. Results of research conducted in the second cycle, it can be concluded that with peneran learning model Cooperative Tepe STAD, the ability of class XI student of SMK 1 Ampibabo determine the plot, characterization and background in the short story "Robohnya Surau Kami" by Ali Akbar Navis can be enhanced through Cooperative Learning Stad.